Hedging in second language writing implications for teaching technical correspondence to Filipino tertiary ESL students (Bulacan State University research journal, 2012)
Scientific writing is indispensable in the academe and that includes even those in the technical fields. Because of the nature of academic life, writing letters and all sorts of correspondence is a must-have skill to make the organization work very efficiently. People in the technical profession are therefore called upon to apply communication skills. But using the said media is not simply stringing words so as to convey message. Effectiveness in sending information will need to apply some underlying principles to improve the constant human interaction. Inability to put thought in words or turn a word-phrase to thinking with similar meanings creates communication failure which results to missed appointments of meaning. A small argument leads to a small degree of confusion making one participant less cooperative. Effective outcome in the communication process is not achieved overnight...